Using virtual reality technology to treat adolescent and young adult depression disorder: a systematic review and meta-analysis - Yilong Pu; Heng Luo (Discover Psychology)
Abstract This study conducted a comprehensive and systematic review of the virtual reality (VR) intervention on depression disorder in adolescents and young adults over the past fourteen years (January 2011 to December 2024). It focused specially on the features of VR and the design of treatment program. A total of 16 relevant articles, encompassing 23 empirical studies, were included. Data were coded and analyzed from five dimensions: metadata information, participant characteristics, research design, technological features, and treatment program design. To test the overall effect of VR technology for adolescent and young adult depression, we conducted a meta-analysis of 19 experimental studies (55 outcomes) of the studies. The results of meta-analysis revealed that VR intervention demonstrated an overall medium effect size (Hedge’s g = 0.486) in treating depression disorder among adolescents and young adult depression. Significant moderating effects were observed for factors such as age group, the number of intervention sessions, the type of VR technology, therapeutic objectives and approaches. Based on these findings, the study offers practical recommendations and directions for future research.